Histiocytic sarcoma with central nervous system involvement in 6 cats. (January 2023) - Riker, Jesse; Clarke, Lorelei L.; Demeter, Elena A.; Miller, Andrew D.; Howerth, Elizabeth W.; Miller, Doris M.; Rissi, Daniel R.
Here we characterize 6 cases (4 autopsies and 2 biopsies) of histiocytic sarcoma in the CNS of cats. All affected cats had chronic, progressive clinical signs. Three autopsied cats were euthanized because of a poor prognosis, and one died. The clinical outcome for the biopsy cases remains unknown. Tumors occurred in the brain (4 cases), spinal cord (1 case), and brain and spinal cord (1 case). Neoplasms were restricted to the CNS in 3 cases. Reported gross changes in the 4 autopsy cases consisted of neuroparenchymal swelling with or without tissue pallor or gray discoloration (2 cases) and a yellow or dark-gray mass (2 cases). Histologically, pleomorphic, round-to-elongate neoplastic cells with typical histiocytic morphology effaced the neuroparenchyma and leptomeninges. Multinucleate neoplastic cells were observed in all cases. The mitotic count was 1–24 in 2.37 mm 2 (10 FN22 40× fields). Neoplastic cells in all cases had positive immunolabeling for Iba1; immunolabeling was negative for E-cadherin, CD3, CD79, and MUM1, confirming their histiocytic origin.